Genetic Ablation of Pyruvate Dehydrogenase Kinase Isoform 4 Gene Enhances Recovery from Hyperoxic Lung Injury: Insights into Antioxidant and Inflammatory Mechanisms - Keisuke Watanabe; Akie Kato; Hiroyuki Adachi; Atsuko Noguchi; Hirokazu Arai; Masato Ito; Fumihiko Namba; Tsutomu Takahashi (Biomedicines, 2024)
Background: Pyruvate dehydrogenase kinase isoform 4 (PDK4) plays a pivotal role in the regulation of cellular proliferation and apoptosis. The objective of this study was to examine whether the genetic depletion of the PDK4 gene attenuates hyperoxia-induced lung injury in neonatal mice. Methods: Neonatal PDK4−/− mice and wild-type (WT) mice were exposed to oxygen concentrations of 21% (normoxia) and 95% (hyperoxia) for the first 4 days of life. Pulmonary histological assessments were performed, and the mRNA levels of lung PDK4, monocyte chemoattractant protein (MCP)-1 and interleukin (IL)-6 were assessed. The levels of inflammatory cytokines in lung tissue were quantified. Results: Following convalescence from neonatal hyperoxia, PDK4−/− mice exhibited improved lung alveolarization. Notably, PDK4−/− mice displayed significantly elevated MCP-1 protein levels in pulmonary tissues following 4 days of hyperoxic exposure, whereas WT mice showed increased IL-6 protein levels under similar conditions. Furthermore, neonatal PDK4−/− mice subjected to hyperoxia demonstrated markedly higher MCP-1 mRNA expression at 4 days of age compared to WT mice, while IL-6 mRNA expression remained unaffected in PDK4−/− mice. Conclusions: Newborn PDK4−/− mice exhibited notable recovery from hyperoxia-induced lung injury, suggesting the potential protective role of PDK4 depletion in mitigating lung damage.